Azo-Schiff base derivatives of transition metal complexes as antimicrobial agents - Pervaiz, Muhammad; Sadiq, Sahar; Sadiq, Amber; Younas, Umer; Ashraf, Adnan; Saeed, Zohaib; Zuber, Muhammad; Adnan, Ahmad (Coordination chemistry reviews, 2021)
[Display omitted] •Average global HALE is vulnerable to morbidities mediated by (Antimicrobial Resistant) microbes with their abrupt evolutionary course.•Pharmaceutic potentiality of Azo & Azomethine moieties in Azo-Schiff Base Ligands have been subject of antimicrobial investigations.•Metalation of ASBLs drastically reinforce the antibacterial and antifungal face of parent compounds.•Well-founded approach to design and characterisation of metal derivatives of ASBLs have been extended over the last two decennia. AMR (Antimicrobial-resistant) pathogens like MRSA (Methicillin-Resistant Staphylococcus aureus) have become prodigious peril to human health in the past couple of years with the failure of various antifungals and antibiotics in treating mild to chronic mycoses and septicemia. In the grave concern for the rising contagions, Azo-Schiff Bases with dual functionality and far-ranging pharmacological potential has been considered an excellent target for antimicrobial investigations. A diversity of homocyclic and heterocyclic organic precursors has been utilized for submitting novelty in the Azo-Schiff Base Ligands (ASBLs). In addition, the d-block transition metal chelates of ASBLs with infinitely diverse features have also been synthesized and characterized exploiting the classical and advanced analytical techniques. These resourceful coordination compounds owing to their characteristic polydentate ligands with multiple coordination sites, the geometry of complexes, and redox nature of metal centres are bestowed with the structural tunability to reinvigorate their potential applications. A detailed literature survey divulged that no compendious review has yet been published on ASBL-metal derivatives. Therefore, the present study encompasses the research undertaken during the last two decennia for the development and in vitro antimicrobial screening of these prospective drug agents.